2020
DOI: 10.1017/s0958344020000142
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-technology-induced learning strategies: Chinese university EFL students learning English in an emerging context

Abstract: This article reports on findings regarding the learning strategies used by a group of Chinese English as a foreign language (EFL) learners in a mobile-technology-assisted environment. The research design is a context-specific case study using Dörnyei’s (2005) categories of learning strategies as the conceptual and analytical framework to guide data collection and analysis. Both quantitative and qualitative data were collected through a questionnaire from a sample of 75 Chinese EFL learners and a small-scale fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…However, students showed regular attempts to look for online opportunities to practice their EFL speaking and thus compensating for inadequacies of formal poor in-class practice. Such a finding is commensurate with the notion that self-regulated students use contextual control and monitoring and consider environmental regulation as an essential aspect of their SLR (Diasti and Mbato, 2020;Gao and Shen, 2020;Sun and Wang, 2020;Yu et al, 2019). Besides, it substantiates relevant findings that EFL students who exercise higher environmental regulation could overcome the limitations of their poor formal EFL-input learning environments and find other rich informal EFL-input contexts to practice their EFL speaking (Uztosun, 2020).…”
Section: Junior and Senior Students' Level Of Srmis-eflsupporting
confidence: 75%
See 3 more Smart Citations
“…However, students showed regular attempts to look for online opportunities to practice their EFL speaking and thus compensating for inadequacies of formal poor in-class practice. Such a finding is commensurate with the notion that self-regulated students use contextual control and monitoring and consider environmental regulation as an essential aspect of their SLR (Diasti and Mbato, 2020;Gao and Shen, 2020;Sun and Wang, 2020;Yu et al, 2019). Besides, it substantiates relevant findings that EFL students who exercise higher environmental regulation could overcome the limitations of their poor formal EFL-input learning environments and find other rich informal EFL-input contexts to practice their EFL speaking (Uztosun, 2020).…”
Section: Junior and Senior Students' Level Of Srmis-eflsupporting
confidence: 75%
“…SRM strategies are attempts or tactics that students use to motivate themselves to sustain or enhance their efforts to fulfill particular academic tasks ( Dörnyei, 2009 ; Miele and Scholer, 2017 ; Pintrich, 2004 ; Wolters and Benzon, 2013 ). Students can generate and bolster their self-motivation through controlling and regulating their task value, learning environment, affect, and classroom environment ( Boekaerts and Corno, 2005 ; Gao and Shen, 2020 ; Li, 2017 ; Pintrich, 2004 ; Teng et al., 2020 ; Uztosun, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…One argument in favor of such tools is that they provide language learners with a more flexible, personalized and interactive learning environment (Mondahl & Razmerita, 2014;Pilar et al, 2013), and recent studies have identified the advantages of mobile technologies in assisting language learning in both formal and informal learning settings (e.g. Fouz-González, 2020;Gao & Shen, 2020;Jin, 2017;Loewen et al, 2019). However, most of the research focuses on how emerging technologies are embedded with teaching and learning four basic language skills, which has left motivation as an area in MALL that needs more scholarly exploration (Gillespie, 2020).…”
Section: Introductionmentioning
confidence: 99%